تحليل الاستبيان باستخدام برنامج spss - ‫مسعود‬ ‬, ‫ربيع‬; ‫جرودي‬, ‫رندة‬ (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال; No 03 (2017): مجلة الاقتصاديات المالية البنكية وإدارة الأعمال, 2018)
‫‪‫‪This‬‬ ‫‪article‬‬ ‫‪is‬‬ ‫‪concerned‬‬ ‫‪with‬‬ ‫‪some‬‬ ‫‪fundamental‬‬ ‫‪ideas‬‬ ‫‪of‬‬ ‫‪analysis‬‬ ‫‪of‬‬ ‫‪data‬‬ ‫‪from‬‬ ‫‪surveys.‬‬ ‫‪The‬‬ ‫‪discussion‬‬ ‫‪is‬‬ ‫‪at‬‬ ‫‪a‬‬ ‫‪statistically‬‬ ‫‪simple‬‬ ‫‪level.‬‬ ‫‪Our‬‬ ‫‪aim‬‬ ‫‪here‬‬ ‫‪is‬‬ ‫‪to‬‬ ‫‪clarify‬‬ ‫‪the‬‬ ‫‪ideas‬‬ ‫‪that‬‬ ‫‪successful‬‬ ‫‪data‬‬ ‫‪analysts‬‬ usually‬‬ ‫‪need‬‬ ‫‪to‬‬ ‫‪consider‬‬ ‫‪to‬‬ ‫‪complete‬‬ ‫‪a‬‬ ‫‪survey‬‬ ‫‪analysis‬‬ ‫‪task‬‬ ‫‪purposefully.‬‬